2013
DOI: 10.1037/a0029225
|View full text |Cite
|
Sign up to set email alerts
|

An inexpensive family index of risk for mood issues improves identification of pediatric bipolar disorder.

Abstract: Family history of mental illness provides important information when evaluating pediatric bipolar disorder (PBD). However, such information is often challenging to gather within clinical settings. This study investigates the feasibility and utility of gathering family history information using an inexpensive method practical for outpatient settings. Families (N=273) completed family history, rating scales, MINI and KSADS interviews about youths 5–18 (median=11) years presenting to an outpatient clinic. Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Direct interviews with family members would also be helpful, although Gershon and Guroff (1984) have suggested a high specificity of the family history method such that a reported positive is likely to be true. Algorta et al (2013) reported that parental report of psychiatric history provided valid information and helped discriminate pediatric bipolar disorder from other disorders. Some have suggested that cultural biases could account for the findings with Europeans minimizing illness in themselves and other family members.…”
Section: Resultsmentioning
confidence: 98%
“…Direct interviews with family members would also be helpful, although Gershon and Guroff (1984) have suggested a high specificity of the family history method such that a reported positive is likely to be true. Algorta et al (2013) reported that parental report of psychiatric history provided valid information and helped discriminate pediatric bipolar disorder from other disorders. Some have suggested that cultural biases could account for the findings with Europeans minimizing illness in themselves and other family members.…”
Section: Resultsmentioning
confidence: 98%
“…Brief screening tools make adding family history clinically feasible. 122 High EE (ie, criticism, hostility, and emotional overinvolvement) and high family conflict are risk factors for treatment drop-out and more rapid relapse. 90 High-EE families may show larger responses to family-focused psychotherapeutic interventions.…”
Section: | Measurementmentioning
confidence: 99%
“…Again, some investigators question the reliability of this type of family history, but others indicate that it has considerable reliability and validity (Algorta et al, 2011). However, our exclusive use of a parental history of illness, rather than that of any first-degree relative, may also increase accuracy of reporting.…”
Section: Limitationsmentioning
confidence: 99%